Proliferation Of Unlicensed Mining In Indonesia When The Minerba Law Was Enacted - Sri Suatmiati; Feri Tuispani; Reny Okpirianti (Jurnal sosial dan sains, 2022)
Background: Article 33, Section 3 of the 1945 Constitution of the Republic of Indonesia states, "Land and water and the natural resources therein shall be under state control and shall be used for the maximum prosperity of the people." Therefore, according to Article 33, Section 3 of the 1945 Constitution of the Republic of Indonesia, Indonesia's natural resources are managed by the state to benefit the people, as mentioned earlier. Coal production in Indonesia is increasing every year. Purpose: Therefore, the Indonesian government has decided to change the country's primary energy source from petroleum to coal by 2025. Method: The research style employed in this study is normative legal; however, it is supported by data/information from the Directorate General of Mineral and Coal about numerous issues associated with unlicensed mining in Indonesia. Results: Illegal mining must be eradicated through a concerted effort. Improving mining supervision and monitoring aspects, particularly by increasing the quantity and calibre of mining supervision employees, should be a top priority for the government's current preventative measures (mine inspectors). Furthermore, repressive attempts by law enforcement must be addressed seriously, particularly against law enforcement officers who participate in such operations. In addition, illegal mining must be prosecuted by addressing multiple elements, including legal, law enforcement, infrastructure, community, and cultural factors. Conclusion : In this instance, the House of Representatives of the Republic of Indonesia must urge the government to adopt a fiscal policy that better supports the facilities and equipment of law enforcement officers in the mining industry. This is important to tackle various challenges associated with the monitoring and monitoring requirements of mining activities.